Isolation of mutants with abnormal petal epidermal cell morphology. (2nd November 2017) - Saffer, Adam M.; Irish, Vivian F.
ABSTRACT: Plants consist of many different cell types with specific shapes optimized for their particular functions. For example, most flowering plants have conically shaped epidermal cells on the upper surface of their petals that are important for pollinator attraction. The control of cell morphology in organs such as roots and leaves has been extensively studied, but much less is known about the genes that promote conical expansion of petal epidermal cells. We have developed a technique to rapidly assay the morphology of conical petal epidermal cells, and we employed this method in an unbiased genetic screen to identify mutants that alter the development of these cells. Mutants isolated in this screen affected cell shape, cell size, cuticle synthesis, and cellular chirality. This approach allowed for the identification of novel cellular components that are critical for the morphology of conical petal cells, and demonstrates the usefulness of petal epidermal cells as a model system for studying cellular morphogenesis.